“I Feel Like a Different Woman”: Negotiating Gender and Motherhood in the Context of Transnational Migration from Axochiapan, Morelos, to Minneapolis, Minnesota - Palmerin Velasco, Diana G. (Journal of the Motherhood Initiative for Research and Community Involvement, 2013)
To explore if, in effect, in the context of transnational migration ‘traditional’ notions of gender and motherhood are re-defined, this article compares the before and after migration lived experiences of a group of Mexican mothers who migrated from Axochiapan, Morelos to Minneapolis, Minnesota. The main thesis, on which this paper is based, consists of arguing for the adoption of a view capable of providing us with the necessary insights to further explore the transnational emotional ties evoked in the redefinition of ‘traditional’ notions of gender and motherhood. According to the collected narratives and in line with the conclusions reached by other studies in the subject, the main challenge faced by migrant mothers who crossed the border without their children, is the difficulty to overcome the resentment and strain caused by physical separation. However, and without minimizing the importance of this aspect, we also found that migration presented an opportunity to turn around some of the early gendered norms, values and practices learnt in Axochiapan that, before crossing the border, had a negative impact on the self-perception of the participants as women and mothers.